2012
DOI: 10.7314/apjcp.2012.13.2.479
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Soy Isoflavone Food on Survival of Breast Cancer Patients in China

Abstract: Aim: Soy foods are the major source of isoflavones, which are believed to play important roles in genesis of breast cancer and its progression. We here conducted a prospective study to evaluate the association of soy isoflavone food consumption with breast cancer prognosis. Methods: A prospective study was performed from January 2004 and January 2006 in China. Trained interviewers conducted face-to-face interviews using a structured questionnaire to collect information on dietary habits and potential confoundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 15 publications
(16 reference statements)
2
64
0
1
Order By: Relevance
“…And another study conducted by Fink et al (Fink et al, 2007) reported that reduced hazard ratios [hazard ratio (95% confidence interval)] for all-cause mortality were observed among premenopausal and postmenopausal women for the highest quintile of intake prior to cancer diagnosis, compared with the lowest, for isoflavones [0.52 (0.33-0.82)]. Regarding to the associations between soy food intake after cancer diagnosis and survival (mortality or recurrence), the results were not the same based on available cohort studies (Guha et al, 2009;Shu et al, 2009;Kang et al, 2010;Caan et al, 2011;Nechuta et al, 2012;Zhang et al, 2012). One meta-analysis of four prospective cohort studies (Boyapati et al, 2005;Fink et al, 2007;Guha et al, 2009;Shu et al, 2009) showed that soy isoflavones intake was inversely associated with risk of breast cancer recurrence (Dong et al, 2011).…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…And another study conducted by Fink et al (Fink et al, 2007) reported that reduced hazard ratios [hazard ratio (95% confidence interval)] for all-cause mortality were observed among premenopausal and postmenopausal women for the highest quintile of intake prior to cancer diagnosis, compared with the lowest, for isoflavones [0.52 (0.33-0.82)]. Regarding to the associations between soy food intake after cancer diagnosis and survival (mortality or recurrence), the results were not the same based on available cohort studies (Guha et al, 2009;Shu et al, 2009;Kang et al, 2010;Caan et al, 2011;Nechuta et al, 2012;Zhang et al, 2012). One meta-analysis of four prospective cohort studies (Boyapati et al, 2005;Fink et al, 2007;Guha et al, 2009;Shu et al, 2009) showed that soy isoflavones intake was inversely associated with risk of breast cancer recurrence (Dong et al, 2011).…”
Section: Introductionmentioning
confidence: 69%
“…After reading full-texts, we excluded reviews (n =47), experimental studies (n =88) and not about survival (n=41). Finally, five cohort studies (six citations (Guha et al, 2009;Shu et al, 2009;Kang et al, 2010;Caan et al, 2011;Nechuta et al, 2012;Zhang et al, 2012)) (11206 patients) were included.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of breast carcinogenesis is still not fully understood. Breast cancer may result from multiple environmental, dietary, hereditary, racial and socioeconomic risk factors (Ronco et al, 2012a;Ronco et al, 2012b;Zhang et al, 2012;Zhou et al, 2012a;Zhou et al, 2012b;Shamsi et al, 2013;Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%